Once again, how useful are social desirability scales for measuring response distortion on personality questionnaires? - Galić, Zvonimir; Jerneić, Željko (2010)
A recent study among researchers experienced in using personality tests showed that most of them favor the use of corrections for response distortion on personality questionnaires. This finding is surprising considering that it seems at odds with studies showing that correcting for socially desirable responding, neither results in more accurate personality descriptions nor improves validities of personality traits in predicting various job related outcomes. However, considering recent developments in social desirability conceptualization and measurement maybe correction should still not be dismissed. Recently was a new social desirability model proposed (Paulhus, 2002, 2006). According to that model, deliberate self-presentation in favorable light is not one-(unfavorable-favorable) but two-dimensional, and should be measured with two impression management scales differing in content. The first is communal management scale which measures respondent’s tendency for denying socially deviant impulses and claiming saint-like attributes and the second, agentic management scale, indicates the level of exaggeration of one’s intellectual and social competency. The aim of this study was to test whether this new impression management scales (Paulhus, 2006) represent valid indicators of response distortion on personality scales. A within-subject design study was conducted during which 213 participants completed a five factor personality questionnaire and social desirability inventory, both in honest and “fake-good” conditions. The results showed that impression management scales scores gained in “fake-good” condition only weakly correlated with direct indicators of response distortion on personality scales, defined as a difference score between faked and honest responses on each trait. Moreover, correction for response distortion didn’t make faked personality scores more similar to those gained in honest condition.
Projekt MZOS
ENG